CPUE TREND AND DOMINANT FISHING GEAR OF MACKEREL (Rastrelliger sp.) LANDED IN KARANGANTU - Lana Izzul Azkia; Fitri Afina Radityani; Muhammad Reza (Jurusan Perikanan dan Kelautan, 2023)
PPN Karangantu is one of the fish landing sites in Serang City, Banten Province. One of the most commonly landed fish species at PPN Karangantu is mackerel. Several fishing gears are used by Karangantu fishermen to catch mackerel, including single monofilament gillnets, boat lift nets, lift nets, and lines. While mackerel fishing efforts in the 2017-2021 timeframe are likely to increase, specific management measures for mackerel fishery at Karangantu PPN have not been implemented. The purpose of this study was to determine the CPUE trend for mackerel fisheries in the 2017-2021 timeframe and to identify the dominant types of fishing gear used in mackerel fishery activities. The data used in this study were obtained from the PPN Karangantu statistical report and field observations. The collected data was processed and analyzed using CPUE and descriptive analysis. The results showed that the CPUE trend for mackerel from 2017 to 2021 tends to increase sustainably, with the single monofilament gillnet being the dominant fishing gear used in mackerel fishing.